2002
DOI: 10.1103/physrevb.65.085412
|View full text |Cite
|
Sign up to set email alerts
|

Orientational order of hut clusters grown coherently on the substrate

Abstract: Within the Tersoff approximation we obtain the analytic expressions for the elastic hut-hut and pyramidpyramid interaction energies. Numerous experimental results show that the orientation of a Ge hut ridge is either parallel or perpendicular to the ͓010͔ direction of Si, and we treat these two possible hut orientations as spin variables in the two-dimensional ͑2D͒ Ising model. To study the thermal-equilibrium configuration of hut orientations, we map the Hamiltonians of the square-lattice and rectangular-latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…All transport measurements were performed using the standard four probe technique. The measurements were performed either in a conventional 4 He flow cryostat fitted with an 8 T superconducting magnet down to 2 K or in a 3 He cryostat fitted with a 6 T superconducting magnet down to 300 mK.…”
Section: Methodsmentioning
confidence: 99%
“…All transport measurements were performed using the standard four probe technique. The measurements were performed either in a conventional 4 He flow cryostat fitted with an 8 T superconducting magnet down to 2 K or in a 3 He cryostat fitted with a 6 T superconducting magnet down to 300 mK.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the matching effect observed in superconducting films with periodic array of holes, has been a subject of considerable theoretical [1,2,3,4] and experimental attention [5,6,7,8,9,10,11,12,13,14,15,16]. In magnetic fields, matching effect manifests as a periodic variation of superconducting transition temperature (T c ) and critical current (I c ) with a period commensurate with integer number of flux quantum (Φ 0 ) passing through each unit cell.…”
Section: Lettermentioning
confidence: 99%
“…A film with periodic array of holes can be visualized as a periodic network of side sharing loops, provided the width of the superconducting region is smaller than the Ginzburg-Landau coherence length (ξ). It has been theoretically shown that in such networks quantum interference (QI) effects would also give rise to T c oscillations similar to single-loop Little Parks [3], though additional weaker structures could appear at non-integral rational fractions of flux filling [4]. The second mechanism is related to vortex pinning.…”
Section: Lettermentioning
confidence: 99%
See 2 more Smart Citations